Predictors of Postoperative Outcome in Emergency Laparotomy for Perforation Peritonitis; a Retrospective Cross-sectional Study - Rai, Ankit; Huda, Farhanul; Kumar, Praveen; Elizabath David, Lena; S, Chezhian; Basu, Somprakas; Singh, Sudhir (Archives of Academic Emergency Medicine, 2022)
Introduction: Hollow viscus perforation is a significant cause of surgical mortality. Various attempts have been made to identify high-risk patients preoperatively and optimize and manage such patients more aggressively. This study aimed to evaluate the predictors of outcome in patients undergoing emergency laparotomy for perforation peritonitis. Methods: This retrospective cross-sectional study was conducted on perforation peritonitis cases admitted to the Department of General Surgery, All India Institute of Medical Sciences, Rishikesh, India. The association between preoperative patient variables with postoperative complications, anastomotic leaks, need for intensive care unit (ICU) admission, and 30-day mortality were evaluated. Results: Tachycardia at the time of admission (t = 2.443, p = 0.020), hypotension (χ2 = 18.214, p = <0.001), lower haemoglobin (t = -4.134, p = <0.001), higher blood urea nitrogen levels (W = 1967.000, p = 0.012), International Normalised Ratio (INR) ≥ 1.5 (χ2 = 17.340, p = <0.001), the mean albumin level 2.89 ± 0.77 g/dL (t = -2.348, p = 0.027), and delay in surgery (χ2 = 28.423, p = 0.008) were significant associate factors of mortality. The association between need for ICU admission and higher pulse rate on admission (W = 2782.500, p = 0.011), lower systolic blood pressure (W = 1627.500, p = 0.029), higher blood urea nitrogen (W = 2299.000, p = 0.030) and serum creatinine levels (W = 2192.500, p = 0.045), preoperative coagulopathy (χ2 = 6.773, p = 0.017), hypoalbuminemia (t = -2.515, p = 0.016), and delay in surgery (χ2 = 17.780, p = 0.016) was significant. Conclusion: Based on the results of this study, hypotension, azotaemia, coagulopathy, and delay in surgery, increase the risk of postoperative mortality of patients undergoing emergency laparotomy for perforation peritonitis. Tachycardia, hypotension, azotaemia, hypoalbuminemia, and pre-operative coagulopathy were good predictors of need for ICU admission. Shock at presentation, deranged renal function and coagulopathy were associated with an increased risk of postoperative complications.